2018
DOI: 10.1063/1.5038947
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of infrared imaging video bolometer for application to deuterium experiment on the large helical device

Abstract: An infrared imaging video bolometer was improved for application to a neutron environment in fusion plasma devices, i.e., the Large Helical Device (LHD). In order to calibrate the thermal characteristics of the activated foil absorber inside the plasma vacuum vessel, the remote-controlled in situ calibration system was improved with high-surface-flatness mirrors. Furthermore, the carbon coating method was improved by introducing a vacuum evaporation technique instead of the conventional spray technique to real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Blackening of the foil is also an important aspect for IRVB. In this case a vacuum evaporated carbon coating has been developed which significantly enhanced reproducibility and uniformity of the calibration process so that uncertainties less than about 10 % could be achieved [31,32].…”
Section: Spectral Sensitivity Of Bolometer Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blackening of the foil is also an important aspect for IRVB. In this case a vacuum evaporated carbon coating has been developed which significantly enhanced reproducibility and uniformity of the calibration process so that uncertainties less than about 10 % could be achieved [31,32].…”
Section: Spectral Sensitivity Of Bolometer Sensorsmentioning
confidence: 99%
“…To tackle the challenging calibration of the IRVB system an improved approach has been presented recently [32]. It is based on a removable unit which can be attached to the IRVB viewing system and uses a visible laser of known power to illuminate individual pixels of the detection foil.…”
Section: Irvb Concept For Itermentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is too costly, especially for radiation profile measurement with a number of channels. On the other hand, InfraRed imaging Video Bolometer (IRVB) can realize a multi-dimensional measurement using only a foil absorber and an infrared (IR) camera [5][6][7][8][9]. Preliminary results of an IRVB on GAMMA10/PDX suggested that the sensitivity of the IRVB should be improved to realize the sensitivity comparable to that of the measurement on the Large Helical Device, LHD.…”
Section: Introductionmentioning
confidence: 99%